Desenvolvimento de um método para potencializar os estudos de programação competitiva no ensino médio e fundamental - Menezes, Giullia Rodrigues (2024)
A good study track, dedication and technical support throughout its completion are important factors for good results in computer programming competitions. Dedicating yourself to your studies is a great way to improve your performance and win awards in competitions. Exploring these particularities and based on the profile of Brazilian medalists in the Brazilian Computing Society programming championships, this research developed and improved a method capable of preparing students for competitive programming. The improvement of the study method was carried out in several application cycles and methods for validating and identifying possible improvements, thus making it increasingly better and more adapted to the reality and needs of students. After their applications, the students who participated in the training noticed an improvement in their performance in competitions and this was demonstrated in the results when they won awards in programming competitions, such as the Brazilian Informatics Olympiad (OBI), the Women's Computing Tournament (TFC ) (current OBI Women's Competition - CF-OBI), and the international competition of the Iberoamerican Informatics Olympiad (OII). The results are significant when compared with the results of previous years. There were 11 winners in total; 5 in OBI 2023; 5 in CF-OBI 2023; and 1 in OII 2022, this being the best result in the historical series of previously tried methods. The awards are indicators of the good performance of training students in programming competitions, which reinforces the effectiveness of the method developed in this research and how promising it can be when applied on a larger scale.